2017
DOI: 10.1088/1757-899x/223/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of ground tire rubber devulcanization using twin screw extruder and internal mixer

Abstract: Abstract. Devulcanization of ground tire rubber (GTR) was done using twin screw extruder (TSE) and internal mixer (IM). Processing parameters were varied to analyze its effect on gel content. Fourier Transform Infrared Spectroscopy (FTIR) analysis was performed as qualitative technique to confirm structural change. The devulcanized rubbers with the least gel content percentage produced in both TSE and IM were then used as filler in natural rubber (NR)/coconut coir (CC) composite preparation. Effects of gel con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…They obtained a gel content of approximately 75% in the most aggressive condition. On the other hand, Ujianto et al [6], using twin screw extruders, reached gel values of approximately 50%, from samples with 85% gel content at 300°C and 100 rpm. Taking as a basis that the speed used in the extrusion is 100 rpm, and resulted in a rate of the same magnitude as that in the thermokinetic mixer, the speeds are about 50 times more significant, but the temperature reached in the times studied is much lower than at 300°C, the shear rate is believed to play an essential role in reducing the gel content as it results in greater chain scissions.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…They obtained a gel content of approximately 75% in the most aggressive condition. On the other hand, Ujianto et al [6], using twin screw extruders, reached gel values of approximately 50%, from samples with 85% gel content at 300°C and 100 rpm. Taking as a basis that the speed used in the extrusion is 100 rpm, and resulted in a rate of the same magnitude as that in the thermokinetic mixer, the speeds are about 50 times more significant, but the temperature reached in the times studied is much lower than at 300°C, the shear rate is believed to play an essential role in reducing the gel content as it results in greater chain scissions.…”
Section: Resultsmentioning
confidence: 93%
“…Ujianto and coworkers compared elastomer devulcanization using single and twin screw extruders. They reported that the twin screw extruder operating at 300°C and 100 rpm reduced the gel content by 50% for an elastomer with an initial gel content of 85%, while for the single screw, the reduction was 40% [6]. Diaz et al performed thermomechanical devulcanization of waste tires and compared two mixers, one with high shear and the other with pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Ujianto et al [ 9 ], using twin-screw extruders, reached gel values of approximately 50%, from samples with 85% gel content at 300 °C and 100 rpm. Considering that the speed used in extrusion is 100 rpm and that in the thermokinetic mixer, the degree of devulcanization is similar.…”
Section: Resultsmentioning
confidence: 99%
“…Ujianto and coworkers compared elastomer devulcanization using single- and twin-screw extruders. They reported that the twin-screw extruder operating at 300 °C and 100 rpm reduced the gel content by 50% for an elastomer with an initial gel content of 85%, while for the single-screw, the reduction was 40% [ 9 ]. Diaz et al performed thermomechanical devulcanization of waste tires and compared two mixers, one with high shear and the other with pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Ujianto et al [23] 2017 It focuses on FT-IR of NR Qualitative analysis, aiming at the evaluation of spectrometric changes, resulting from devulcanization. Datta et al [24] 2017 Determination of NR, SBR and BR contents in ternary mixture by FT-IR and TGA.…”
Section: Authormentioning
confidence: 99%